Variation in the parasite community of the sardine fish Triportheus nematurus (Actinopterygii: Characidae) from the Medalha lagoon in the Pantanal wetland, Brazil. Issue 3 (18th March 2013) - Costa-Pereira, R.; Paiva, F.; Tavares, L.E.R.
Abstract: In July 2009 and July 2010 (two dry periods separated by an atypically large flood in the Pantanal wetland of Brazil), 34 and 33 specimens of the sardine fish Triportheus nematurus were collected, respectively, for the study of the metazoan parasite community of this species. Parasite ecological and community descriptors were calculated for both host samples, and possible similarities were tested statistically. Five species of metazoan parasites were identified, four of which were common to both host samples. A total of 61 metazoan parasites were collected from all fish hosts (17 specimens in July 2009 (mean: 0.5 ± 0.66 parasites/fish) and 44 specimens in July 2010 (mean: 1.33 ± 1.41 parasites/fish)). The nematode Procamallanus hilarii and the monogenean Anacanthorus sp. were the most prevalent and abundant species in 2009 and 2010, respectively. The mean total abundance and species richness were significantly higher in 2010. Parasite communities in both samples of T. nematurus were characterized by species with low prevalence, abundance, mean total abundance and species richness, thus indicating low parasite diversity. Significant differences in the prevalence and abundance of P. hilarii and Anacanthorus sp. between the two samples allowed the discrimination of infracommunities, which were united in two distinct groups. This appears to be the first evidence that the peculiar hydrological dynamics of the southern Pantanal wetland (Brazil) exert an important influence over the structure of the parasite community.